Síntese e análise estrutural de clusters binários e ternários derivados de bis(fenilselenolato) de mercúrio Hg(SePh)2 - Stieler, Rafael (2012)
This work deals with the synthesis and structural analysis of binary and ternary clusters derivatives from mercury bis(phenylselenolate) - Hg(SePh)2. The reaction of Hg(SePh)2 with Mg(II), Fe(II), Co(II) and Ni(II) metal salts led to the formation of a series of binary clusters [M(DPPMO2)3][Hg4X4(SePh)6]·4DMF·H2O and [M(DMF)6][Hg8SeX4(SePh)12]. The reaction of Hg(SePh)2 with Cu(I) phosphine complexes led to the formation of a series of ternary clusters [HgCu2X2(SePh)2(PPh3)4] and [Hg6Cu4(SePh)16]. When Hg(SePh)2 was reacted with Co(II) and Ni(II) thiocyanide complexes, the heterometallic coordination polymers [M(DMF)2(NCS)4(HgSePh)2]n were obtained. Furthermore, the formation of a by-product [Hg3(SePh)5(O2SePh)]n was observed. It is formed by the oxidation of the phenylselenolate ligand. A structural study in the solid state of these compounds was carried out using single crystal X-ray diffraction. Other analytical methodologies such as powder X-ray diffraction, elemental analysis and infrared spectroscopy were also used for the characterization of the compounds. The band gap in the solid state was measured for the obtained clusters compounds through ultraviolet-visible spectroscopy.